Assessing the potential of activated carbons from polyethylene terephthalate (PET) as adsorbents to separate co2 from flue gas - Moura, Pedro Augusto Silva de (2017)
The Greenhouse Effect is a serious problem that concerns all countries and a solution to minimize or slow down this effect is mandatory. Increases in temperature and sea water level have caused some relevant impacts that can be felt by most of the world population. Carbon Dioxide (CO2) is claimed as one of the main causes of this effect. Another problem in our society is the increasing production of Polyethylene Terephthalate (PET) polymers along the years, mainly used as soft drink bottles. Post-consumption bottles disposal is a huge problem to the world. The production of activated carbons from PET wastes generates materials with interesting properties for gas adsorption and storage. The aim of this work is to assess the potential of these activated carbons from PET (ACPXs) as adsorbents to separate CO2 from flue gas. ACPXs have an exceptionally high surface area with pore sizes concentrated in a very narrow range (0.5-2 nm) and a hydrophobic surface with nearly no functional groups. Increasing burn-off degrees (22, 41 and 76%) led to adsorbents with a broader pore size distribution (PSD), but all mainly in the range of micropores. Single gas and mixed gas isotherms with CO2 and N2 reveal that the samples have an interesting selectivity for flue gas separation. These adsorbents have a high affinity for CO2, ACPX-76 reaching an adsorption uptake of 6.323 mmol g-1 at 4 bar and 298 K. On the other hand, sample ACPX-22 has a higher narrow microporosity proportion (97.3%), which in turn gives a higher selectivity for CO2 over N2 (15.98 at 4 bar and 298 K). The differential adsorption enthalpy curves are typical of highly microporous samples reaching values close to those found in zeolites (40 kJ mol-1) for low loadings, going down to values only slightly above the neat of condensation of CO2 (17 kJ mol-1) at higher loadings. It was found that the higher the burn-off, the wider the PSD and hence the greatest CO2 capacity may be achieved. Nevertheless, higher CO2/N2 selectivities are found for the less activated sample, which has the lowest burn-off, lowest CO2 uptake and the narrower Pore Size Distribution (PSD). The best trade-off of these parameters (working capacity, selectivity and adsorption enthalpy) was found for sample ACPX-41, with an intermediate burn-off, by comparison of an adsorbent performance indicator (API), as proposed in the literature.